Investigating the Performance of Microbial Fuel Cells in Wastewater Treatment Containing Azo Dyes Using Meta-Analysis - Sina Parsayan; Shabnam Sadri Moghaddam (آب و توسعه پایدار)
Colored wastewater containing azo dyes is an important source of pollution and discharging it without treatment leads to severe problems. A microbial fuel cell is a new solution that treats wastewater and generates electricity simultaneously and is variable in terms of configuration and operating conditions. Meta-analysis is a statistical technique that combines the results of multiple scientific studies on a question. In this study, the configuration and operating conditions were investigated according to the volumetric treatment rate and normalized energy recovery based on operating volume and dye concentration changes. Factors such as the number of chambers, shape of the anode electrode, COD source, and hydraulic retention time were considered. The single-chamber mode showed better performance than the two-chamber mode due to the more available space of the electrolyte and the absence of the proton exchange membrane. Contrary to previous reports, smooth electrodes were superior to the brush mode. Glucose is a better COD source than acetate due to producing more electrons and hydrogen ions during substrate decomposition. Since the decomposition of 90% of the dye occurs in the first 24 hours, the hydraulic retention time in a state that is less than or equal to 24 hours, the process shows better performance. Also, the relation between the organic loading rate resulting from azo dye and the volumetric treatment rate was obtained, which includes the relationship between hydraulic retention time and changes in dye concentration. In the end, a framework for reporting information needed for a more detailed investigation of microbial fuel cells was presented.